Impact of Divergent Thinking Training on Teenagers’ Emotion and Self-Efficacy During the COVID-19 Pandemic - Zuo, Bin; Wang, Qi; Qiao, Yalan; Ding, Yu; Wen, Fangfang (Frontiers in Psychology, 2021)
Currently due to COVID-19 pandemic, there is a tendency of a decrease in self-efficacy and an increase in anxiety among people. Though previous studies have shown that self-efficacy and creativity training are positively related, little is known about the impact of creativity training on self-efficacy and anxiety. Therefore, our study aims to search for the answer, and to support people injured psychologically in this tough period. We randomly assigned 70 students to a 2 (time: pretest, post-test) × 2 (groups: creativity training, controlled) mixed design. Participants in the experimental group were given a nine-day creativity training with the theme of “writing down 10 novel functions of the mask” while those in the control group spent 10 minutes recording the food they ate every day. Self-efficacy and anxiety of these two groups were measured before and after training. Our results showed that compared to the experimental group, self-efficacy decreased while anxiety increased for the control group. These findings suggest that creativity training exerts a positive effect on teenagers. Implications and limitations are discussed.